THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND THEIR TRANSLATION ABILITY - Faridah Oktari; Mukhrizal Mukhtar; Arasuli Arasuli (Universitas Galuh, 2019)
This research attempted to investigate the students’ grammar mastery, their translation ability, and the correlation between both variables. The research was designed as a quantitative correlational method. The population was 79 sixth semester students of English Education Study Program of Bengkulu University in the academic year 2018/2019. The samples were 40 students. The instruments used to collecting the data were grammar test and translation test. The collected data were analyzed by Pearson Product Moment Formula using Statistical Package for Social Sciences (SPSS) software version 16.0. The results of this research showed: 1. Majority of the student (77.5%) had poor grammar mastery. 2. Majority of the students (82.45%) had inadequate translation ability. 3. There is a correlation between students’ grammar mastery and their translation ability (the correlation coefficient is 0.797). Therefore, it was concluded that the students’ grammar mastery contributed significantly to their translation ability. Lastly, it was suggested that English Education Study Program should add semester credit units (SKS) of the grammar and translation subjects in order to improve the students’ grammar mastery and translation ability. Keywords: Correlation, Students’ Grammar Mastery, Students’ TranslationAbility